The effect of seismic design on total cost of structural work for medium rise apartment building - Nur Shairah, Zulkhibri; Mohd Irwan, Adiyanto; Hanis Athirah, Roslan (IOP Publishing, 2024)
People believed Malaysia did not experience earthquakes because the country is not in the Pacific Ring of Fire. Then, an earthquake of magnitude Mw 6.0 struck Ranau, Sabah, meaning Malaysia was no longer safe from seismic catastrophes. This is especially true when most buildings in Malaysia are not made to withstand the shaking that comes from earthquakes. Considering the seismic design will mean using higher steel reinforcement, immediately raising costs. Hence, this paper studies the cost effect on Sabah's 6-story reinforced concrete (RC) apartment building. The study had three levels of reference peak ground acceleration: agR= 0.08 g, 0.12 g, and 0.16 g, and thesoil type was D which was classified as Ductility Class Medium (DCM). In thecomparison between the non-seismic and seismic models, the findings suggested that the amount of steel reinforcement per 1 m3 of concrete increased by 7% and 31%, respectively. Other than that, the cost increment of structural work increased by 3.3% to 12.7% compared to the non-seismic model.